RETRACTED ARTICLE: GLOBALIZATION AND ITS IMPACT ON ECONOMIC GROWTH: EVIDENCE FROM ASEAN COUNTRIES - Martini, Martini (TRIKONOMIKA, 2020)
This article has been retracted as a result of multiple publications from the article by the relevant author. Similar articles can be found at the URL http://journal.umpo.ac.id/index.php/ekuilibrium/article/view/1586